A method for preparing a high-copper copper-aluminum drawing-rolling composite forming composite strip
Patent Information
- Application Number
- CN202611167848.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-16
AI Technical Summary
然而,单纯的直接压扁轧制面临着显著的材料不相容挑战:在缺乏侧向刚性约束的平面应变压缩状态下,内部较软的铝芯容易发生横向的非均匀展宽
[0012] (1) It is beneficial to improve forming stability and reduce the risk of excessive local thinning of the copper cladding layer: The present invention adopts a composite forming process of "circular die drawing and diameter reduction - flat die drawing and forming - continuous rolling". The copper-clad aluminum composite round wire after circular die drawing and diameter reduction is further pre-formed by flat die, so that it is transformed from a circular cross-section to a rectangular surface before entering the continuous rolling of flat rolls. Compared with the round composite wire directly entering the flat roll rolling, this process advances the main shape transformation of the circular cross-section to the strip cross-section to the flat die drawing stage, so that the subsequent flat roll rolling mainly realizes the gradual thinning and widening of the rectangular initial billet, which is beneficial to reduce the non-uniform deformation caused by the severe cross-section reconstruction in the first pass and the risk of excessive local thinning of the copper cladding layer. Combined with the reasonable distribution of the reduction rate in subsequent multiple passes, a copper-aluminum composite strip with a more uniform copper layer distribution and a more stable composite interface can be obtained.
Smart Images

Figure CN122913275A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal composite material forming technology, and more specifically, to a method for preparing a high copper-to-aluminum drawing-rolling composite strip. Background Technology
[0002] Copper-clad aluminum (CCA) composite conductors combine the excellent conductivity and contact reliability of pure copper with the low density and low cost advantages of pure aluminum, making them a key lightweight material to replace pure copper conductors in the electrical engineering field. Traditional micro-CCA wires mostly adopt a "thin copper cladding layer" design, with the copper layer volume ratio typically limited to between 10% and 15%. With the increasing demand for lightweight conductors and high current-carrying capacity in high-power drive motors for new energy vehicles and aerospace electrical systems, the development of "high copper ratio" composite flat wires with a cross-sectional mass ratio approaching 1:1 has become an industry trend (it should be noted that "high copper ratio" means that the mass ratio of the copper cladding layer to the inner aluminum core is close to 1:1; based on the difference in density between the two at room temperature, the corresponding theoretical volume ratio is approximately 23% copper and 77% aluminum).
[0003] Under room temperature cold working conditions, copper exhibits significantly higher deformation resistance than aluminum. Existing technologies for preparing ultra-fine, high-copper-ratio CCA flat wires primarily employ multi-pass direct flat-roll cold rolling processes. However, simple direct flattening rolling faces significant material incompatibility challenges: under plane strain compression without lateral rigidity constraints, the softer aluminum core is prone to lateral, non-uniform widening. This uncontrolled lateral flow pulls on the harder outer copper layer, causing localized passive thinning of the copper layer, which can easily lead to interface instability and increase the probability of "aluminum leakage" manufacturing defects. Furthermore, relying solely on intense cold continuous rolling often results in a significant decrease in material plasticity, typically making it difficult to balance strength and ductility. Therefore, the field requires a process route that can effectively constrain core flow and improve interface stability. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing a high copper-to-aluminum drawing-rolling composite strip.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] A method for preparing a high copper ratio copper-aluminum drawing-rolling composite strip involves drawing a copper-clad aluminum composite round wire with a round die to reduce its diameter; drawing the reduced copper-clad aluminum composite round wire with a flat die to obtain a rectangular blank; and continuously rolling the rectangular blank with four passes of flat rolls to obtain a high copper ratio copper-aluminum drawing-rolling composite strip.
[0007] Furthermore, the diameter of the copper-clad aluminum composite round wire is 0.9~1.1mm, and the mass ratio of the copper cladding layer to the aluminum core is (0.9~1.1):1.
[0008] Furthermore, the diameter of the copper-clad aluminum composite round wire after being drawn and reduced by a circular die is reduced to 0.85~0.98mm.
[0009] Furthermore, the rectangular blank obtained after being drawn by a flat die has a thickness of 0.45~0.55mm and a width of 1.4~1.6mm.
[0010] Furthermore, the reduction rates for each pass are controlled sequentially to be 38%~42%, 33%~37%, 28%~33%, and 5%~10%, ultimately producing a high copper-to-aluminum drawing-rolling composite strip with a thickness of 0.10~0.15mm and a width of 2.8~3.2mm.
[0011] In summary, the present invention has the following beneficial effects:
[0012] (1) It is beneficial to improve forming stability and reduce the risk of excessive local thinning of the copper cladding layer: The present invention adopts a composite forming process of "circular die drawing and diameter reduction - flat die drawing and forming - continuous rolling". The copper-clad aluminum composite round wire after circular die drawing and diameter reduction is further pre-formed by flat die, so that it is transformed from a circular cross-section to a rectangular surface before entering the continuous rolling of flat rolls. Compared with the round composite wire directly entering the flat roll rolling, this process advances the main shape transformation of the circular cross-section to the strip cross-section to the flat die drawing stage, so that the subsequent flat roll rolling mainly realizes the gradual thinning and widening of the rectangular initial billet, which is beneficial to reduce the non-uniform deformation caused by the severe cross-section reconstruction in the first pass and the risk of excessive local thinning of the copper cladding layer. Combined with the reasonable distribution of the reduction rate in subsequent multiple passes, a copper-aluminum composite strip with a more uniform copper layer distribution and a more stable composite interface can be obtained.
[0013] (2) It helps to achieve a synergistic improvement in strength and plasticity: The present invention introduces a more complex strain path through the design of the integrated drawing-rolling composite forming process, which not only strengthens the matrix texture, but also forms an obvious deformation coordination effect in the interface area, thereby generating an additional strengthening effect; at the same time, the moderate strain path deflection induces a soft cubic texture in the copper layer, which helps to alleviate local deformation concentration and improve the plasticity of the material; the synergistic effect of the two makes the product achieve a high yield strength while maintaining a good fracture elongation. Attached Figure Description
[0014] Figure 1 This is a schematic diagram showing the evolution curve of stress in the X direction over time during the rolling process of a typical tracking unit of the composite strip prepared in Comparative Example 1 under finite element simulation, and its position distribution in the finite element model. Figure 1The numbers 1-21 on the right side represent the sampling points of the tracking unit in the finite element simulation. Figure 1 In the left-hand section, legend 1, 5, 9, 13, and 21 represent the sampling points 1, 5, 9, 13, and 21 of the tracking unit.
[0015] Figure 2 This is a schematic diagram showing the evolution curve of stress in the Y direction over time during the rolling process of a typical tracking unit of the composite strip prepared in Comparative Example 1 under finite element simulation, and its position distribution in the finite element model. Figure 2 The numbers 1-21 on the right side represent the sampling points of the tracking unit in the finite element simulation. Figure 2 In the left-hand section, legend 1, 5, 9, 13, and 21 represent the sampling points 1, 5, 9, 13, and 21 of the tracking unit.
[0016] Figure 3 This is a schematic diagram showing the evolution curve of stress in the X direction over time and its position distribution in the finite element model of a typical tracking unit of the composite strip prepared in Example 1 during the drawing-rolling composite forming process. Figure 3 The numbers 1-21 on the right side represent the sampling points of the tracking unit in the finite element simulation. Figure 3 In the left-hand section, legend 1, 5, 9, 13, and 21 represent the sampling points 1, 5, 9, 13, and 21 of the tracking unit.
[0017] Figure 4 This is a schematic diagram showing the evolution curve of stress in the Y direction over time and its position distribution in the finite element model of a typical tracking unit of the composite strip prepared in Example 1 during the drawing-rolling composite forming process. Figure 4 The numbers 1-21 on the right side represent the sampling points of the tracking unit in the finite element simulation. Figure 4 In the left-hand section, legend 1, 5, 9, 13, and 21 represent the sampling points 1, 5, 9, 13, and 21 of the tracking unit.
[0018] Figure 5 Comparative figures show the evolution of the longitudinal section morphology of the copper / aluminum composite interface in Comparative Example 1 and Example 1 during multi-pass rolling. Figure 5 (a) Part - Figure 5 (d) shows the longitudinal section morphology of the copper / aluminum composite interface after the composite billet of Comparative Example 1 was rolled in the first, second, third and fourth passes. Figure 5 (e) Part - Figure 5 (h) shows the longitudinal section morphology of the copper / aluminum composite interface after the rectangular billet obtained by flat die drawing in Example 1 was rolled in the first, second, third and fourth passes.
[0019] Figure 6 Electron backscattering diffraction (EBSD) results of the final cross-section of the composite bands prepared in Comparative Example 1 and Example 1 (Figure 1) Figure 6 (a) is a phase distribution diagram of the composite belt prepared in Comparative Example 1. Figure 6 (b) is a phase distribution diagram of the composite belt prepared in Example 1. Figure 6 (c) is the inverse pole diagram of the composite band prepared in Comparative Example 1. Figure 6 (d) is the inverse pole diagram of the composite band prepared in Example 1. Figure 6 (e) is a diagram of a triangular inverse polar chart.
[0020] Figure 7 The nuclear average orientation difference (KAM) diagrams and the relative frequency distribution diagrams of local orientation deviations of the composite belts prepared in Comparative Example 1 and Example 1 are shown. Figure 7 (a) is a diagram showing the average orientation difference of the nuclei in the longitudinal section of the composite band prepared in Comparative Example 1. Figure 7 (b) is a diagram showing the average orientation difference of the nuclei in the longitudinal section of the composite belt prepared in Example 1. Figure 7 (c) is a local orientation deviation relative frequency distribution diagram of the copper layer prepared in Comparative Example 1. Figure 7 (d) is a local orientation deviation relative frequency distribution diagram of the copper layer in the composite strip prepared in Example 1. Figure 7 (e) is a local orientation deviation relative frequency distribution diagram of the aluminum layer of the composite strip prepared in Comparative Example 1. Figure 7 (f) is a local orientation deviation relative frequency distribution diagram of the composite aluminum layer prepared in Example 1.
[0021] Figure 8 The micro-orientation distribution function (ODF) profiles of the copper and aluminum layers of the composite strips prepared in Comparative Example 1 and Example 1 are shown below. Figure 8 (a) is a cross-sectional view of the micro-orientation distribution function of the composite copper layer prepared in Comparative Example 1. Figure 8 (b) is a cross-sectional view of the micro-orientation distribution function of the composite aluminum layer prepared in Comparative Example 1. Figure 8 (c) is a cross-sectional view of the micro-orientation distribution function of the composite copper layer prepared in Example 1. Figure 8 (d) is a cross-sectional view of the micro-orientation distribution function of the composite aluminum layer prepared in Example 1. Figure 8 (e) is a schematic diagram of the main texture components and β-fiber skeleton lines of face-centered cubic (FCC) metal.
[0022] Figure 9 The actual stress-strain curves of the composite belts prepared in Comparative Example 1 and Example 1 under room temperature tension are shown. Detailed Implementation
[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] The method for preparing the high copper ratio copper-aluminum drawing-rolling composite strip of the present invention is as follows:
[0025] Using copper-clad aluminum composite round wire with a diameter of 0.9~1.1mm as raw material, wherein the mass ratio of copper cladding to aluminum core is (0.9~1.1):1, the diameter of the copper-clad aluminum composite round wire is reduced to 0.85~0.98mm by circular drawing with a circular die. The reduced-diameter copper-clad aluminum composite round wire is then drawn into shape using a flat die under external traction force, changing its cross-section from circular to rectangular. The cross-section is shaped to prepare a rectangular billet with a thickness of 0.45~0.55mm and a width of 1.4~1.6mm. The obtained rectangular billet is subjected to four passes of continuous flat roll rolling, with the reduction rate of each pass controlled successively at 38%~42%, 33%~37%, 28%~33% and 5%~10%, finally producing a high copper ratio copper-aluminum drawing-rolling composite strip with a thickness of 0.10~0.15mm and a width of 2.8~3.2mm.
[0026] Example 1
[0027] (1) Take a copper-clad aluminum composite round wire with an outer diameter of 1.0 mm (i.e., oxygen-free copper / pure aluminum (Cu-OFHC / Al-1060) composite round wire with a copper to aluminum mass ratio of 1:1) and clean its surface.
[0028] (2) Circular die drawing and diameter reduction: The oxygen-free copper / pure aluminum composite circular wire is fed into a drawing die with a hole diameter of 0.95mm for drawing deformation (so that the wire diameter is changed from 1.0mm to 0.95mm) to control the initial stress / strain state of the copper layer.
[0029] (3) Flat die drawing: The copper-clad aluminum composite round wire with a diameter of 0.95 mm obtained in step (2) is further drawn using a flat die. Under the action of external traction force, the wire passes through the flat die along the axial direction, so that its cross-section gradually changes from a circle to a rectangle, and finally a rectangular blank with a thickness of 0.48 mm and a width of 1.50 mm is obtained. This step enables the round composite wire drawn by the round die to complete the cross-sectional shape transformation in advance before entering the subsequent flat roll continuous rolling, so that the subsequent rolling mainly realizes the gradual thinning and widening of the rectangular blank, avoiding the first flat roll from simultaneously bearing the severe cross-sectional shape transformation and large thickness compression.
[0030] (4) The rectangular billet is subjected to four passes of continuous flat roll rolling with reduction rates of 39.3%, 35.2%, 30.9% and 7.7% respectively, and finally a composite strip with a thickness of 0.12 mm and a width of 3.0 mm is obtained.
[0031] Comparative Example 1
[0032] Prepared according to the method of Example 1, the difference is that steps (2) and (3) are omitted, that is, after step (1) is completed, step (4) is directly entered to perform four-pass continuous rolling. In order to obtain the same final thickness and width as in Example 1, the reduction rate of the four passes is set to 40%, 40%, 46.4% and 37.8% respectively, and rolled into a composite strip with a thickness of 0.12 mm and a width of 3 mm.
[0033] Results analysis:
[0034] Table 1 shows the Cu layer texture volume fraction test results of the composite tapes prepared in Comparative Example 1 and Example 1 in the final pass; Table 2 shows the Al layer texture volume fraction test results of the composite tapes prepared in Comparative Example 1 and Example 1 in the final pass; and Table 3 shows the tensile mechanical property test results of the composite tapes prepared in Comparative Example 1 and Example 1.
[0035] Table 1
[0036]
[0037] Table 2
[0038]
[0039] Table 3
[0040]
[0041] Figure 1 This is a schematic diagram showing the evolution curve of stress in the X direction over time during the rolling process of a typical tracking unit of the composite strip prepared in Comparative Example 1, and its position distribution in the finite element model. Figure 1 The numbers 1-21 on the right side represent the sampling points of the tracking unit in the finite element simulation. Figure 1 In the left part of the figure, legend 1, 5, 9, 13 and 21 represent the sampling points 1, 5, 9, 13 and 21 of the tracking unit. Figure 2 This is a schematic diagram showing the evolution curve of stress in the Y direction over time in a typical tracking unit of the composite strip prepared in Comparative Example 1 during the rolling process, and its position distribution in the finite element model. Figure 2 The numbers 1-21 on the right side represent the sampling points of the tracking unit in the finite element simulation. Figure 2In the left part of the figure, legend 1, 5, 9, 13 and 21 represent the sampling points 1, 5, 9, 13 and 21 of the tracking unit. Figure 3 This is a schematic diagram showing the evolution curve of stress in the X direction over time and its position distribution in the finite element model of a typical tracking unit of the composite strip prepared in Example 1 during the drawing-rolling composite forming process. Figure 3 The numbers 1-21 on the right side represent the sampling points of the tracking unit in the finite element simulation. Figure 3 In the left part of the figure, legend 1, 5, 9, 13 and 21 represent the sampling points 1, 5, 9, 13 and 21 of the tracking unit. Figure 4 This is a schematic diagram showing the evolution curve of stress in the Y direction over time and its position distribution in the finite element model of a typical tracking unit of the composite strip prepared in Example 1 during the drawing-rolling composite forming process. Figure 4 The numbers 1-21 on the right side represent the sampling points of the tracking unit in the finite element simulation. Figure 4 In the left part of the figure, legend 1, 5, 9, 13 and 21 represent the sampling area points 1, 5, 9, 13 and 21 of the tracking unit.
[0042] Based on the finite element simulation results, it can be seen that ( Figures 1-4 In Comparative Example 1, the soft aluminum core is excessively widened laterally, passively stretching the copper layer. In Example 1, the pre-deformation by drawing is combined with subsequent continuous rolling, ensuring a relatively stable stress distribution in the composite billet during subsequent forming. Example 1 also pre-shapes the circular cross-section into a rectangular initial billet by drawing with a flat die before continuous flat-roll rolling, reducing the severe cross-section reconstruction borne by the first pass of flat-roll rolling. Compared to Comparative Example 1, the complete process route of this invention achieves a more uniform copper layer thickness distribution and a more stable copper-aluminum interface, which is beneficial for suppressing aluminum leakage defects and improving the stability of the composite interface.
[0043] Figure 5 Comparative figures show the evolution of the longitudinal section morphology of the copper / aluminum composite interface in Comparative Example 1 and Example 1 during multi-pass rolling. Figure 5 (a) Part - Figure 5 (d) shows the longitudinal section morphology of the copper / aluminum composite interface after the composite billet of Comparative Example 1 was rolled in the first, second, third and fourth passes. Figure 5 (e) Part - Figure 5(h) shows the longitudinal section morphology of the copper / aluminum composite interface after the rectangular billet obtained by flat die drawing in Example 1 was rolled in the first, second, third, and fourth passes. It can be seen that the composite strip prepared in Comparative Example 1 exhibits "V"-shaped necking instability in the first pass, making it highly susceptible to "aluminum leakage." In contrast, the composite strip prepared in Example 1 has a uniform copper layer thickness distribution in each pass, and the interface forms a wavy mechanical interlocking structure, reducing the risk of aluminum leakage. This result indicates that the combined process of "circular die drawing for diameter reduction—flat die drawing—continuous rolling" is beneficial for improving the cross-sectional forming stability during subsequent rolling processes and reducing the risk of excessive local thinning of the copper cladding layer and aluminum leakage.
[0044] Figure 6 Electron backscattering diffraction (EBSD) results of the final cross-section of the composite bands prepared in Comparative Example 1 and Example 1 (Figure 1) Figure 6 (a) is a phase distribution diagram of the composite belt prepared in Comparative Example 1. Figure 6 (b) is a phase distribution diagram of the composite belt prepared in Example 1. Figure 6 (c) is the inverse pole diagram of the composite band prepared in Comparative Example 1. Figure 6 (d) is the inverse pole diagram of the composite band prepared in Example 1. Figure 6 (e) is a diagram of a triangular inverse polar chart. Figure 7 The nuclear average orientation difference (KAM) diagrams and the relative frequency distribution diagrams of local orientation deviations of the composite belts prepared in Comparative Example 1 and Example 1 are shown. Figure 7 (a) is a diagram showing the average orientation difference of the nuclei in the longitudinal section of the composite band prepared in Comparative Example 1. Figure 7 (b) is a diagram showing the average orientation difference of the nuclei in the longitudinal section of the composite belt prepared in Example 1. Figure 7 (c) is a local orientation deviation relative frequency distribution diagram of the copper layer prepared in Comparative Example 1. Figure 7 (d) is a local orientation deviation relative frequency distribution diagram of the copper layer in the composite strip prepared in Example 1. Figure 7 (e) is a local orientation deviation relative frequency distribution diagram of the aluminum layer of the composite strip prepared in Comparative Example 1. Figure 7 (f) is a local orientation deviation relative frequency distribution diagram of the composite aluminum layer prepared in Example 1. Figure 6 and Figure 7 The results show that, compared with Comparative Example 1, the local orientation difference distribution near the interface of the composite strip prepared in Example 1 is more uniform, and the high KAM region is significantly reduced. This indicates that the drawing-rolling composite forming process is beneficial to alleviate the local deformation concentration in the interface region and improve the deformation coordination of the copper-aluminum composite interface.
[0045] Figure 8The micro-orientation distribution function (ODF) profiles of the copper and aluminum layers of the composite strips prepared in Comparative Example 1 and Example 1 are shown below. Figure 8 (a) is a cross-sectional view of the micro-orientation distribution function of the composite copper layer prepared in Comparative Example 1. Figure 8 (b) is a cross-sectional view of the micro-orientation distribution function of the composite aluminum layer prepared in Comparative Example 1. Figure 8 (c) is a cross-sectional view of the micro-orientation distribution function of the composite copper layer prepared in Example 1. Figure 8 (d) is a cross-sectional view of the micro-orientation distribution function of the composite aluminum layer prepared in Example 1. Figure 8 (e) is a schematic diagram of the main texture components and β-fiber skeleton lines of face-centered cubic (FCC) metal. Figure 8 The ODF data show that the composite band prepared in Example 1 strengthens the β-orientation lines (copper texture up to 2.78%) representing the strength and induces a soft cubic texture with a volume fraction of 6.05%, which helps to reduce the concentration of local orientation differences near the interface.
[0046] Figure 9 The figures show the true stress-strain curves of the composite strips prepared in Comparative Example 1 and Example 1 under room temperature tension. It can be seen that the tensile yield strength (TYS) of the composite strip prepared in Comparative Example 1 is 222.49 MPa, the ultimate tensile strength (UTS) is 264.01 MPa, and the elongation at break is 2.12%. In contrast, the composite strip prepared in Example 1 shows significant improvements: the tensile yield strength increases to 285.15 MPa, the ultimate tensile strength reaches 319.18 MPa, and the elongation at break increases to 2.61%. The results indicate that the process of this invention can significantly improve the comprehensive mechanical properties of composite materials, achieving synergistic optimization of strength and plasticity.
[0047] In Example 1, the copper cladding layer of the composite strip continuously coats the outer side of the inner aluminum core, and the thickness ratio of the thinnest to the thickest point of the copper layer on its cross-section is ≥0.85. Microstructural observation and image acquisition were performed using an Olympus BX51TRF optical microscope. The observation results showed that the copper layer and aluminum core interface were well bonded, with no obvious defects or abnormal structures observed. The copper cladding layer exhibited a distinct crystallographic oriented fibrous texture and contained 5.0%–8.0% by volume soft cubic texture ({001}). <100> ).
[0048] The copper-aluminum composite strip prepared by the method of this invention has an ultimate tensile strength ≥310MPa, a tensile yield strength ≥280MPa, and an elongation at break ≥2.5% at room temperature. It can be applied to the manufacture of high-power drive motor coil windings for new energy vehicles, high-frequency electromagnetic interconnects for aerospace equipment, and lead frames for high-end electronic packaging.
[0049] Detection method:
[0050] EBSD data acquisition was performed on a ZEISS Sigma 360 field emission scanning electron microscope (FE-SEM) equipped with the appropriate probe. The test area was selected as the longitudinal section of the final pass sample, with a magnification of 3000x and a step size of 0.07 μm. Uniaxial tensile mechanical property tests were conducted using an electronic universal testing machine (e.g., 1000N range) to obtain the yield strength, tensile strength, and elongation at break of the samples. The test environment was room temperature, and the strain rate was set to 1×10⁻⁶. -3 ·s -1 The final pass texture volume fraction test method uses Channel 5 software to analyze and export EBSD data.
[0051] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a high copper-to-aluminum drawing-rolling composite strip, characterized in that, The copper-clad aluminum composite round wire is drawn and reduced in diameter using a round die; the drawn and reduced copper-clad aluminum composite round wire is then drawn into a rectangular blank using a flat die; the rectangular blank is then subjected to four passes of continuous flat roll rolling to obtain a composite strip with a high copper ratio, formed by copper-aluminum drawing-rolling.
2. The method for preparing a high copper-to-aluminum drawing-rolling composite strip according to claim 1, characterized in that, The diameter of the copper-clad aluminum composite round wire is 0.9~1.1mm, and the mass ratio of the copper cladding layer to the aluminum core is (0.9~1.1):
1.
3. The method for preparing a high copper-to-aluminum drawing-rolling composite strip according to claim 1, characterized in that, The diameter of the copper-clad aluminum composite round wire after being drawn and reduced by a circular die is reduced to 0.85~0.98mm.
4. The method for preparing a high copper-to-aluminum drawing-rolling composite strip according to claim 1, characterized in that, The rectangular blank obtained after being drawn by a flat die has a thickness of 0.45~0.55mm and a width of 1.4~1.6mm.
5. The method for preparing a high copper-to-aluminum drawing-rolling composite strip according to claim 1, characterized in that, The reduction rates for each pass are controlled sequentially at 38%~42%, 33%~37%, 28%~33%, and 5%~10%, ultimately producing a high copper-to-aluminum drawing-rolling composite strip with a thickness of 0.10~0.15mm and a width of 2.8~3.2mm.